The signature of all things [compact disc, unabridged] : a novel - Gilbert, Elizabeth, 1969- (Penguin Audio, 2013)
Spanning much of the eighteenth and nineteenth centuries, the novel follows the fortunes of the extraordinary Whittaker family as led by the enterprising Henry Whittake, a poor-born Englishman who makes a great fortune in the South American quinine trade, eventually becoming the richest man in Philadelphia. Born in 1800, Henry's brilliant daughter, Alma (who inherits both her father's money and his mind).